Accelerated loop-mediated isothermal amplification method for the rapid detection of Streptococcus suis serotypes 2 and 14 based on single nucleotide polymorphisms - Meng, Jiajia; Li, Chunling; Wang, Yu; Bian, Zhibiao; Chu, Pinpin; Zhai, Shaolun; Yang, Dongxia; Song, Shuai; Li, Yan; Jiang, Zhiyong; Zhang, Kunli; Li, Yugu; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus suis serotypes 2 and 14 are the most prevalent zoonotic strains. The establishment of a sensitive and extremely accurate method for point-of-care testing for Streptococcus suis serotype 2 and 14 strains is highly desirable. In this study, a loop primer probe-introduced loop-mediated isothermal amplification assay was developed to differentiate Streptococcus suis serotypes 2 and 14 based on SNP (single nucleotide polymorphism). The specific fluorescent probes were designed for the SNP site specific for serotype 2 and 14 Streptococcus suis cpsK genes, and the loop primer probe-introduced loop-mediated isothermal amplification (LAMP) assay was developed using the specific cleavage properties of the RNase H2 enzyme. Rapid and efficient LAMP assays were realized through the use of loop forward primers and stem forward primers. The results showed that the amplification reaction can be performed efficiently at 59°C. The results can be real-time detected or judged using a smartphone and a 3D-printed visualization cassette. The sensitivity of the LAMP assay can reach 18.4 CFU within 40 minutes. The detection rate of the assay system was evaluated using 19 clinical samples with suspected Streptococcus suis infection, and the detection rate was consistent with the sequencing method, suggesting that the test is highly practical. The LAMP assay for Streptococcus suis serotypes 2 and 14 established in this study has strong specificity, high sensitivity, and simple operation, while the reaction can be performed at an isothermal temperature and is not dependent on complex instruments or professional operators, making it suitable for field testing.